MANAJEMEN KOMITE SEKOLAH DALAM PENGUATAN KUALITAS LAYANAN PENDIDIKAN DI MIN 1 BARITO TIMUR TAHUN 2024 - Kasroni, Imam; Susanto, Didi; Rasuna, Rasuna (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
ABSTRACT This study aims to analyze the role of school committee management in strengthening the quality of educational services at MIN 1 Barito Timur in 2024. The research focuses on three main aspects: (1) the implementation of school committee management, (2) supporting and inhibiting factors in educational services, and (3) efforts by the school committee to enhance the quality of educational services. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation. The research informants include the school principal, the head of the school committee, committee members, teachers, and administrative staff. The collected data were analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The study concludes that the management of the school committee at MIN 1 Barito Timur plays a significant role in improving the quality of educational services through teacher competency enhancement, community involvement in facility provision, and the optimization of committee functions as stipulated in Ministry of Education and Culture Regulation No. 75 of 2016. Supporting factors include effective communication, commitment to educational quality, and the committee's dedication to resolving educational issues. However, challenges arise from limited time, budget, facilities, and the availability of professional teachers. Improvement efforts are carried out by providing input in planning, supporting school programs, supervising activities, and mediating between the school, parents, and the community. This study recommends enhancing collaboration between the school and the committee, allocating funds for human resource development, and strengthening the committee's role in supporting educational programs. Keywords: school committee management, educational services, education quality, MIN 1 Barito Timur. ABSTRAK Penelitian ini bertujuan untuk menganalisis peran manajemen komite sekolah dalam penguatan kualitas layanan pendidikan di MIN 1 Barito Timur tahun 2024. Fokus penelitian ini mencakup tiga aspek utama: (1) penerapan manajemen komite sekolah, (2) faktor pendukung dan penghambat dalam layanan pendidikan, dan (3) upaya komite sekolah dalam penguatan kualitas layanan pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi. Informan penelitian terdiri atas kepala sekolah, ketua komite, anggota komite sekolah, guru, dan tata usaha. Data yang diperoleh dianalisis secara deskriptif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Penelitian ini menyimpulkan bahwa manajemen komite sekolah di MIN 1 Barito Timur berperan penting dalam penguatan kualitas layanan pendidikan melalui peningkatan kompetensi guru, keterlibatan masyarakat dalam pengadaan fasilitas, dan optimalisasi fungsi komite sesuai Permendikbud No. 75 Tahun 2016. Faktor pendukung meliputi komunikasi yang baik, komitmen terhadap mutu pendidikan, dan keseriusan komite dalam menyelesaikan masalah, sementara kendala mencakup keterbatasan waktu, anggaran, fasilitas, dan jumlah guru profesional. Upaya perbaikan dilakukan dengan pemberian pertimbangan dalam perencanaan, dukungan terhadap program sekolah, pengawasan kegiatan, dan mediasi antara sekolah, orang tua, serta masyarakat. Penelitian ini merekomendasikan peningkatan kolaborasi antara pihak sekolah dan komite, pengalokasian dana untuk pengembangan SDM, serta penguatan peran komite dalam mendukung program pendidikan. Kata Kunci: manajemen komite sekolah, layanan pendidikan, kualitas pendidikan, MIN 1 Barito Timur